2014
DOI: 10.1590/s0103-84782014000500008
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de nutrientes e produtividade de crambe em função da fertilização com torta de mamona e serpentinito

Abstract: Acúmulo de nutrientes e produtividade de crambe em função da fertilização com torta de mamona e serpentinito.Ciência Rural, v.44, n.5, mai, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The average stem dry matter yield in the clayey soil was 4.19 and 4.65 g/plant in the medium textured soil (Table 2). Prates et al (2014) reported a stem dry matter yield of 1.56 and 4.02 g crambe/plant with the application of silicate, with and without the application of sulfur, respectively. Fruit dry matter averaged 3.33 g/plant in the clayey soil and 3.31 g/plant in the medium textured soil.…”
Section: Resultsmentioning
confidence: 99%
“…The average stem dry matter yield in the clayey soil was 4.19 and 4.65 g/plant in the medium textured soil (Table 2). Prates et al (2014) reported a stem dry matter yield of 1.56 and 4.02 g crambe/plant with the application of silicate, with and without the application of sulfur, respectively. Fruit dry matter averaged 3.33 g/plant in the clayey soil and 3.31 g/plant in the medium textured soil.…”
Section: Resultsmentioning
confidence: 99%
“…Até o momento não há relatos de trabalhos que avaliaram o crescimento da cultura do crambe através da utilização de lodo de esgoto doméstico como fonte de nutrientes. Entretanto, já é bem conhecido o uso de fontes alternativas à fertilizantes químicos para promover a fertilização para essa cultura (PRATES et al, 2014;FREDIANI et al, 2012).…”
Section: Fvunclassified
“…Serpentinite, an inexpensive mineral and in some cases a waste, is formed by a Si oxide tetrahedral sheet bound to Mg(OH) 2 based octahedral layer [16]. Serpentinite has been used in simple applications such as construction, steel mills, magnesium production [17], fertilizer [18] and for CO 2 storage [17,19]. Serpentinite can be a very versatile precursor to produce Mg based materials since under controlled thermal treatment, the Mg 3 Si 2 O 5 (OH) 4 phase dehydrates to produce different Mg containing phases such as dispersed MgO, Mg 2 SiO 4 besides other SiO 2 based phases.…”
Section: Introductionmentioning
confidence: 99%